NAVIGATING THE TAPESTRY OF INTERCULTURAL COMMUNICATION: BUILDING BRIDGES IN A DIVERSE WORLD - Normatova, Aziza (Educational Research in Universal Sciences, 2024)
Intercultural communication stands at the intersection of human interaction, where diverse cultures, languages, and perspectives converge. In our increasingly interconnected world, the ability to navigate and comprehend the intricacies of intercultural communication becomes not only valuable but essential. This article delves into the complexities, challenges, and strategies of intercultural communication, highlighting its significance in fostering empathy, promoting inclusivity, and bridging divides across global communities.